ASSESSING AND MANAGING TERRITORIAL CAPITAL FOR RURAL TOURISM DEVELOPMENT: FINDINGS FROM FIELD RESEARCH IN AZANJA (REPUBLIC OF SERBIA) - Dejanović, Aleksandar; Lukić Nikolić, Jelena; Ljubojević, Ljubomir (Economics of Agriculture, 2024)
This paper investigates the potential for rural tourism development in Azanja (Republic of Serbia) by analyzing its territorial capital - natural, social, cultural, economic and human capital. Results from field research conducted in 2024 encompassing 209 residents revealed that the main strength lies in Azanja’s social capital, followed by natural and cultural capital. However, economic and human capital were identified as weak points, hindering rural tourism development. The results showed that rural tourism development in Azanja requires strategic investments and capacity building to overcome its economic and human capital limitations. Recommendations include fostering local entrepreneurship, providing financial incentives for tourism-related businesses, and implementing educational programs to enhance residents’ knowledge and skills in tourism management and hospitality. By identifying the strengths and weaknesses of Azanja’s territorial capital, this research provides a basis for formulating targeted strategies to enhance the region’s appeal to tourists and foster sustainable rural tourism development.